The effect of tocotrienol-rich fraction on the expression of glutathione S-transferase isoenzymes in mice liver - Ahmed Atia,; Nadia Salem AlRawaiq,; Azman Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Glutathione S-transferase isoenzymes (GSTs) catalyze the conjugation reaction between glutathione and electrophilic compounds. GSTs are involved in the detoxification of toxic and carcinogenic compounds, thus protecting the body from toxic injuries. Tocotrienols are part of the vitamin E family and is believed to possess potent antioxidant activity. The objective of this study was to determine the effect of increasing doses of tocotrienol rich fraction (TRF) supplementation on liver GSTs gene and protein expression. A total of 30 male ICR white mice were divided into five groups (n=6 for each group) and given treatment for 14 days through oral supplementation. Groups were divided as follows: - three groups administered with TRF at doses of 200, 500 and 1000 mg/kg, respectively, a positive control group administered with 100 mg/kg butylated hydroxyanisole (BHA) and a control group administered with only the vehicle (corn oil). At day 15, the mice were sacrificed and their livers isolated. Total RNA was extracted from the liver and quantitative real-time polymerase chain reaction (qPCR) assays were performed to analyze GSTs gene expression. Total liver protein was also extracted and the protein expression of GSTs was determined by Western blotting. The results showed that TRF oral supplementation caused a significant dose-dependent increase in liver GST isoenzymes gene and protein expression, compared to controls. In conclusion, TRF oral supplementation for 14 days resulted in increased gene and protein expression of GST isoenzymes in mice liver dose-dependently, with the highest expression seen in mice treated with 1000 mg/kg TRF.